2015
DOI: 10.1177/0300985815594849
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Exercise and Intra-articular Site on Canals in Articular Calcified Cartilage of Equine Third Carpal Bones

Abstract: The third carpal bone (C3) responds to exercise by adaptive modeling of bone and articular calcified cartilage along the dorsal load path. Canals penetrating articular calcified cartilage, thought to contain vascular tissue, are reported in numerous species. Their significance remains unclear. Our objective was to determine if the number of canals was significantly different in strenuously exercised and control young horses and in a site of intermittent high loading compared to sites sustaining lower habitual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…13,23,46,82 A separate study in a different set of samples confirmed the presence of similar extruded mineralized matrix extending from cracks in the calcified cartilage into the deeper regions of hyaline cartilage, corresponding to sites of superficial hyaline cartilage erosion and fibrillation. 31 Other studies performed in carpal bones of both Thoroughbred and Standardbred racehorses identified subchondral bone sclerosis with increased mineral density, and increases in biochemical markers of bone turnover, corresponding to gross and histologic lesions of cartilage degeneration and osteoarthritis. 22,79 Additional studies attempting to mimic early stages of "naturally occurring" repetitive impact trauma induced by conditioning exercise in 1.5-2-y-old Thoroughbred fillies showed significantly higher bone mineral density in C3, 24 as well as mechanical and morphologic differences in the hyaline and mineralized articular cartilage within sites that withstand high intermittent loads (e.g., dorsodistal Cr and Ci, and dorsoproximal C3).…”
Section: Degenerative Osteoarthritismentioning
confidence: 96%
See 2 more Smart Citations
“…13,23,46,82 A separate study in a different set of samples confirmed the presence of similar extruded mineralized matrix extending from cracks in the calcified cartilage into the deeper regions of hyaline cartilage, corresponding to sites of superficial hyaline cartilage erosion and fibrillation. 31 Other studies performed in carpal bones of both Thoroughbred and Standardbred racehorses identified subchondral bone sclerosis with increased mineral density, and increases in biochemical markers of bone turnover, corresponding to gross and histologic lesions of cartilage degeneration and osteoarthritis. 22,79 Additional studies attempting to mimic early stages of "naturally occurring" repetitive impact trauma induced by conditioning exercise in 1.5-2-y-old Thoroughbred fillies showed significantly higher bone mineral density in C3, 24 as well as mechanical and morphologic differences in the hyaline and mineralized articular cartilage within sites that withstand high intermittent loads (e.g., dorsodistal Cr and Ci, and dorsoproximal C3).…”
Section: Degenerative Osteoarthritismentioning
confidence: 96%
“…13,23,46,82 A separate study in a different set of samples confirmed the presence of similar extruded mineralized matrix extending from cracks in the calcified cartilage into the deeper regions of hyaline cartilage, corresponding to sites of superficial hyaline cartilage erosion and fibrillation. 31 Other studies performed in carpal bones of both Thoroughbred and Standardbred racehorses identified subchondral bone sclerosis with increased mineral density, and increases in biochemical markers of bone turnover, corresponding to gross and histologic lesions of cartilage degeneration and osteoarthritis. 22,79…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation